2018
DOI: 10.3390/jcm8010016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sarcopenia on Sleep Disturbance in Patients with Chronic Liver Diseases

Abstract: We sought to investigate the influence of sarcopenia as defined by muscle strength and skeletal muscle mass (SMM) on sleep disturbance as evaluated by the Japanese version of Pittsburgh Sleep Quality Index (PSQI-J) in chronic liver diseases (CLDs) (n = 419). Muscle strength and muscle mass were determined by grip strength (GS) and SMM using bioimpedance analysis. Patients were classified into four types: type A (n = 61); decreased GS and decreased SMM; type B (n = 45); decreased GS and non-decreased SMM; type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…However, to our knowledge, scarce data of the association in sleep disorder and frailty in patients with CLD are available. Patients with CLD are often suffering from long-standing disease burden, which may affect sleep quality [ 22 ]. In our data, the median sleep duration in a day was 6.5 h, which is almost identical to the average sleep duration of Japanese adults.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, to our knowledge, scarce data of the association in sleep disorder and frailty in patients with CLD are available. Patients with CLD are often suffering from long-standing disease burden, which may affect sleep quality [ 22 ]. In our data, the median sleep duration in a day was 6.5 h, which is almost identical to the average sleep duration of Japanese adults.…”
Section: Discussionmentioning
confidence: 99%
“…They included both inpatients and outpatients. Liver cirrhosis (LC) was determined as demonstrated previously [ 22 ]. Frailty was determined using the following five phenotypes: body weight (BW) loss without intention, exhaustion, muscle strength decline [grip strength (GS) < 26 kg in males and < 18 kg in females], slow walking speed (WS, < 1.0 m/s), and low physical activity (being unable to do light exercise).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We assessed the nutritional status of cirrhotic patients using various methods (9)(10)(11), and a dietitian in our department took anthropometric measurements from all patients. In this study, we evaluated the nutritional status of histologically confirmed cirrhotic patients (F4 stage of the METAVIR scoring system: liver cirrhosis with pseudolobules) (12) and compared the physical data automatically provided with the BIA method to the manually obtained ones by a trained healthcare professional.…”
mentioning
confidence: 99%
“…In our previous investigation, we reported that GS had a strong influence especially in the physiological domains in the 36-Item Short-Form Health Survey in patients with CLDs [4]. We also demonstrated that muscle strength decline was closely associated with sleep disorder in patients with CLDs [5], while non-alcoholic fatty liver disease (NAFLD) is reported to be linked to muscular impairment in elderly adults [6,7,8]. Lee et al reported that there were linear decreases in the NAFLD index across incremental GS values [8].…”
Section: Introductionmentioning
confidence: 99%